The General Bilingual Dictionary as a Working Tool in Thème - Meyer, Ingrid (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1988)
AbstractBecause of his lack of native-speaker intuition for the target language, the thème translator requires of the general bilingual dictionary much more explicit lexical information than does his version counterpart. On the basis of a study of lexical errors made by thème translation students, we examine the weaknesses of the general bilingual dictionary for thème, and relate these to either a non-observance of lexicographic principles, or to a lack of such principles. Finally, we propose three teaching strategies to help thème translation students deal with the general bilingual dictionary.